Health Benefits of Probiotics in Sport and Exercise - Non-existent or a Matter of Heterogeneity? A Systematic Review - Heimer, Melina; Teschler, Marc; Schmitz, Boris; Mooren, Frank C. (Frontiers in Nutrition, 2022)
Background: The use of probiotics in sports has been growing in recent years, as up to 50% of athletes suffer from training- and performance-limiting gastrointestinal (GI) problems. Moreover, repeated exhaustive exercise and high training loads may lead to a transiently depressed immune function, associated with an increased risk of upper respiratory tract infection (URTI). Aim: To provide a qualitative analysis of probiotic effects on URTI, GI symptoms and the immune system in healthy individuals under consideration of performance level as main classifier. Methods: A systematic review of the literature was conducted (PubMed, SPORTDiscus with Full Text, Web of Science) to analyze the effects of probiotics in athletes and healthy active individuals on GI problems, URTI, and the immune system. A qualitative synthesis with performance level and treatment duration as main classifiers was performed. Results: Of 41 eligible studies, 24 evaluated the effects of probiotic supplements in athletes, 10 in recreationally active individuals and 7 in healthy untrained adults. Large heterogeneity was observed in terms of probiotic strains, mode of delivery, performance level, treatment duration and outcome assessment. Overall, studies provided inconsistent observations. Conclusion: The effects of probiotics on immune system, URTI, and GI symptoms in athletes, healthy adults and recreationally active individuals remain inconclusive. Based on the analyzed studies and identified parameters, this article provides suggestions to align future research on the effects of probiotics in exercise. PROSPERO, CRD42021245840.